Gaia Giuliani, Monsters, Catastrophes and the Anthropocene: A Postcolonial Critique (Altre Modernità, 2022)
Gaia Giuliani, Monsters, Catastrophes and the Anthropocene: A Postcolonial Critique (London, Routledge, 2021, 223 pp. ISBN 978-113-847-977-7)by Nicoletta Vallorani